Testing the Effect of a Short Cheap Talk Script in Choice Experiments - Jacob Ladenburg; Jens Olav Dahlgaard; Ole Bonnichsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
The application of stated preference methods rests on the assumption that respondents act rationally and that their demand for the non-market good on the hypothetical market is equal to what their real demand would be. Previous studies have shown that this is not the case and this gap is known as hypothetical bias. The present paper attempts to frame the description of the hypothetical market so as to induce more "true market behaviour" in the respondents by including a short Cheap Talk script. The script informs respondents that in similar studies using stated preference methods, people have a tendency to overestimate how much they are willing to pay compared to their actual (true) willingness to pay. Applying a two-split sample approach to a Choice Experiment study focusing on preferences for reducing visual disamenities from offshore wind farms, the Cheap Talk script is found to be a preference mover, but does not affect preferences significantly. Significant effects are found when relating the effect of the Cheap Talk script to the cost levels of the alternatives, in that female respondents are found to choose higher cost alternatives less frequently when presented with the Cheap Talk script, while male respondents are not affected.
Keywords: C10; C51; C90; 330; Cheap Talk; Stated Preferences; Choice Experiment; Hypothetical Bias; Gender